Assessments are Learning Experiences in Medical Education - Anam Gul, Reema Maqbool, Rida-e-Noor, Mohammad Iqbal Khan (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate general concept of assessment among teachers and students. To analyze the productivity in assessments and to know why not assessments become learning experiences. Methods: A cross sectional survey was conducted and three hundred medical students were interviewed using a standardized questionnaire. Questions were based upon views on current methods of assessment and their effectiveness. A few teachers were also interviewed by key informant method to know their views about assessments and flaws on part of teachers as well as students. Result: Majority (95%) of the students studied for their assessments while 24% of them were able to reproduce whatever they had read. The reasons being lack of time (21%), lack of guidance (19%), fear of the examiner (17%), fear of failure(14%), poor time management(14%) and inappropriate text selection(11%). General behavior of the examiner at the time of assessment was confidence breaking (64%), supportive (34%) and offensive (10%). The response of the examiner on a wrong answer was insulting (49%), encouraging (29%), and silent (22%). Forty-six percent of students accepted that they are marked in the assessments according to their performance; 66% students considered assessment a learning experience; 28% called it an ordeal whereas 6% considered these both ordeals and learning experiences. Conclusion: Medical students are uneasy about assessment methodology and expectations of examiners from them.